Quartz sand and method for producing the same

CN122940176APending Publication Date: 2026-10-20HUALU ENG & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611077525.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-20
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0004]本发明的主要目的在于提供一种石英砂及其制备方法,用以解决石英砂纯度较低且高温析晶不均匀的问题

Benefits of technology

[0028]本发明提供的石英砂,通过在二氧化硅基体内部设置方石英晶核,能够为石英砂在高温条件下的晶化提供稳定的析晶基础,改善传统由表层或局部区域优先析晶所导致的析晶不均问题,进而提升石英砂高温析晶的均匀性与稳定性,减小因内外或界面晶化差异带来的热膨胀失配和热应力损伤风险,并有利于提高纯度,提升石英坩埚的强度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

This invention provides a quartz sand and its preparation method. The quartz sand comprises a silica matrix and cristobalite crystal nuclei present within the silica matrix. The quartz sand provided by this invention has high purity and exhibits more uniform high-temperature crystallization, which can improve the strength of the quartz crucible.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of quartz material technology, and particularly relates to a quartz sand and its preparation method. Background Technology

[0002] In the semiconductor manufacturing field, the Czochralski (CZ) process is the core technology for producing large-size single-crystal silicon wafers. In this process, the quartz crucible, as the key container for holding the silicon material and achieving crystal growth, needs to operate for extended periods in a high-temperature environment exceeding 1500°C. Under these extreme conditions, the outer and support layer materials of the quartz crucible must possess the following characteristics: ultra-high purity (>6N grade), excellent high-temperature mechanical strength, and stable crystallization ability. Specifically, the middle and outer layer materials of the quartz crucible must rapidly undergo an amorphous to cristobalite phase transformation at high temperatures, forming a dense crystal framework to resist softening deformation, while simultaneously avoiding thermal stress cracks or bulging caused by uneven crystallization.

[0003] However, in the existing technology, the purity of quartz sand material is low and the high-temperature crystallization is uneven, resulting in low strength of quartz crucibles. Summary of the Invention

[0004] The main objective of this invention is to provide a quartz sand and its preparation method to solve the problems of low purity and uneven high-temperature crystallization of quartz sand.

[0005] In a first aspect, the present invention provides a quartz sand comprising a silica matrix and cristobalite crystal nuclei present within the silica matrix.

[0006] In the quartz sand described above, the cristobalite crystal nuclei account for 0.1-5% of the mass fraction of the quartz sand.

[0007] The quartz sand described above has a particle size of 70-140 mesh.

[0008] And / or, the purity of the quartz sand is ≥99.9999%;

[0009] And / or, the hydroxyl content in the quartz sand is 1~20ppm.

[0010] Secondly, the present invention provides a method for preparing the quartz sand as described above, comprising the following steps:

[0011] In-situ seeding was performed on a raw material system comprising silicate hydrolysate sol, cristobalite crystal nucleus suspension, and acidic catalyst to obtain a doped gel.

[0012] The doped gel was subjected to aging and sintering treatments in sequence to obtain the quartz sand.

[0013] In the preparation method described above, the quartz crystal nuclei in the quartz crystal nuclei suspension account for 0.1% to 5% of the mass fraction of silicon dioxide in the raw material system;

[0014] And / or, the in situ inoculation temperature is 40~70℃, and the in situ inoculation time is 2~12h.

[0015] The preparation method described above involves dispersing quartz crystal nuclei in a solvent and then ultrasonically treating the solution for 30-90 minutes at a power of 500-1200W.

[0016] The solvent includes at least one of anhydrous ethanol, ultrapure water, isopropanol, acetone, and ethylene glycol;

[0017] The Dv50 of the cristobalite crystal nucleus is ≤1μm.

[0018] In the preparation method described above, the cristobalite crystal nucleus is obtained by devitrification of amorphous silicon dioxide;

[0019] The devitrification reaction includes: heating the amorphous silicon dioxide to 1300-1500°C at a heating rate of 2-5°C / min under an oxygen-containing atmosphere, and carrying out the devitrification reaction for 4-12 hours to obtain the cristobalite crystal nucleus;

[0020] The amorphous silicon dioxide has a Dv50 ≤ 50 μm;

[0021] And / or, the purity of the amorphous silicon dioxide is ≥99.9%;

[0022] And / or, the amorphous silica is derived from waste generated during the production of high-purity silica materials.

[0023] The preparation method described above involves mixing silicate ester with ultrapure water at a molar ratio of (4~10):1, adding a hydrolysis catalyst, and then carrying out a hydrolysis reaction at a pH of 1.5~3.0 and a temperature of 40~70℃.

[0024] In the preparation method described above, the hydrolysis catalyst includes at least one of hydrochloric acid and nitric acid;

[0025] And / or, the silicate ester includes at least one of methyl silicate, ethyl silicate, propyl silicate, and butyl silicate.

[0026] In the preparation method described above, the aging treatment temperature is 50~80℃, and the aging treatment time is 12~24h;

[0027] And / or, the sintering process includes: first, subjecting the aged doped gel to a first sintering treatment at 600~900℃ for 2~4h, and then subjecting it to a second sintering treatment at 1050~1150℃ for 2~6h.

[0028] The quartz sand provided by this invention, by setting cristobalite crystal nuclei inside the silica matrix, can provide a stable crystallization basis for the crystallization of quartz sand under high temperature conditions, improve the problem of uneven crystallization caused by preferential crystallization on the surface or in local areas in traditional methods, thereby improving the uniformity and stability of high temperature crystallization of quartz sand, reducing the risk of thermal expansion mismatch and thermal stress damage caused by differences in crystallization inside and outside or at the interface, and is conducive to improving purity and increasing the strength of quartz crucible. Detailed Implementation

[0029] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions in the embodiments of this invention will be clearly and completely described below in conjunction with the embodiments of this invention. Obviously, the described embodiments are only some embodiments of this invention, not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.

[0030] In existing technologies, to meet the high-temperature crystallization requirements of quartz crucible materials, high-purity quartz sand is typically modified using methods such as mineralization-induced crystallization and crystalline phase blending. Mineralization-induced crystallization typically involves adding mineralizing components such as barium, aluminum, and calcium to the quartz sand, using external impurities to lower the crystallization activation threshold, making it easier for the quartz sand to transform from amorphous to crystalline at high temperatures. Crystalline phase blending involves physically mixing cristobalite particles of a certain size with amorphous quartz sand, using the added crystalline phase as a nucleation center to guide subsequent crystallization.

[0031] These methods can improve the crystallization rate of materials to some extent, but they still have significant shortcomings under semiconductor-grade application conditions. First, the addition of mineralizing components introduces impurities, especially metal elements which may migrate in the high-temperature silicon molten environment, compromising the ultra-high purity requirements. Second, physically blended crystalline particles are often discretely distributed with abrupt interfaces, and crystallization usually preferentially grows from the particle surface or local areas, making it difficult to form a uniform and continuous crystalline structure inside the quartz sand particles. This leads to inconsistent thermal expansion behavior inside and outside the particles, between particles, and at the interfaces. Third, when local crystallization is too rapid or the crystallization area is unevenly distributed, stress concentration can be easily induced under high temperature and thermal cycling conditions, causing microcracks, bulging, spalling, or a decrease in mechanical strength. Therefore, existing technologies still struggle to simultaneously meet multiple requirements such as high purity and uniform crystallization.

[0032] Therefore, how to improve the uniformity and stability of high-temperature crystallization of quartz sand while maintaining its high purity, and reduce the thermal stress damage caused by local crystallization and interface mismatch, has become an urgent technical problem to be solved.

[0033] Through extensive research, the inventors of this application discovered that by setting cristobalite crystal nuclei inside a silica matrix, quartz sand can undergo a more stable crystallization response based on the internal crystal nuclei in high-temperature applications. This improves the unevenness caused by traditional external mineralization or surface / local crystallization, maintains the high purity of the material, and enhances the strength of the subsequent quartz crucible.

[0034] In view of this, in a first aspect, the present invention provides a quartz sand comprising a silica matrix and cristobalite crystal nuclei present within the silica matrix.

[0035] In this invention, quartz sand is applied to the outer layer, support layer, or other parts of the quartz crucible used in the Czochralski method for single-crystal silicon growth in the semiconductor material manufacturing field that need to withstand long-term high-temperature heat loads. The silica matrix serves as the main phase of the quartz sand, providing a high-purity, high-temperature resistant chemical composition that is compatible with existing quartz crucible systems. The cristobalite nuclei within this silica matrix provide stable and uniform internal crystallization induction centers under subsequent high-temperature conditions. Compared to simply attaching crystalline particles to the particle surface or physically blending them with quartz sand, this invention embeds the cristobalite nuclei within the silica matrix, allowing crystallization behavior to extend from the particle interior to the surrounding matrix. This makes the crystallization initiation location, crystallization path, and high-temperature phase transformation process more controllable, thereby reducing the problems of inconsistent thermal expansion and stress concentration caused by preferential crystallization in localized areas. Based on the above analysis, it can be seen that the key to this quartz sand is not simply to increase the crystallization rate, but to achieve a more uniform crystallization response within the particle bulk phase while maintaining a high-purity silica system by constructing an internal induced composite microstructure, thereby improving the strength of the subsequent quartz crucible.

[0036] In this invention, the silica matrix can be amorphous silica. The cristobalite nuclei are preferably pure-phase cristobalite nuclei, and their chemical composition is homologous to the silica matrix, both belonging to the SiO2 system. By using homologous silica materials to form the nuclei and matrix, the problem of exogenous impurities caused by the use of mineralizing components such as barium, aluminum, and calcium to promote crystallization can be avoided, and the phenomenon of excessively high interfacial energy between the nuclei and the matrix due to compositional differences can be reduced. Specifically, in a high-temperature environment, the cristobalite nuclei can act as local ordered structural cores, reducing the nucleation barrier required for the transformation of surrounding amorphous SiO2 to a crystalline state. This allows the quartz sand particles to no longer rely primarily on random surface nucleation or local defect nucleation when heated, but rather on bulk phase crystallization triggered by nuclei pre-distributed within the particles. Since the nucleation sites are pre-defined in multiple regions within the particles, the crystallization front can form and advance relatively uniformly within the particles, thereby dispersing and releasing the volume changes and thermal expansion caused by crystallization, thus ensuring the stability of the particle structure under high-temperature thermal cycling conditions.

[0037] This invention utilizes cristobalite nuclei pre-placed within a high-purity silica matrix, employing nucleus-induced nucleation and bulk epitaxial growth mechanisms to enable amorphous SiO2 to undergo crystallization transformation according to a predetermined internal microstructure path during high-temperature applications. Unlike schemes that rely on external mineralizers to lower the crystallization activation threshold, this embodiment does not rely on dissimilar metal elements to alter the chemical reaction environment. Instead, it achieves controllable crystallization through the structural matching relationship between homologous SiO2 crystal phases. Therefore, while meeting the crystallization requirements, it maintains the stringent purity requirements of semiconductor-grade materials.

[0038] Therefore, by embedding cristobalite crystal nuclei inside a silica matrix, this invention enables quartz sand to maintain its ultra-high purity while gaining internal induced crystallization ability. This allows for more uniform and stable bulk crystallization during high-temperature service, reducing thermal stress damage caused by local crystallization and interface mismatch, and improving the high-temperature structural stability, resistance to softening deformation, and long-term service life of the outer or supporting layer of the quartz crucible.

[0039] In some embodiments of the present invention, the mass fraction of cristobalite nuclei in quartz sand is 0.1-5%, for example, it can be a range of 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5% or any two of these.

[0040] By limiting the content of cristobalite crystal nuclei within the above-mentioned range, this invention ensures that the number of cristobalite crystal nuclei is sufficient to provide stable nucleation centers during subsequent high-temperature processing, while avoiding insufficient crystallization induction due to insufficient content, or crystal nuclei agglomeration, local structural imbalance, and purity risks due to excessive content.

[0041] In some embodiments of the present invention, the particle size of the quartz sand is 70 to 140 mesh, for example, it can be a range of 70 mesh, 80 mesh, 90 mesh, 100 mesh, 110 mesh, 120 mesh, 130 mesh, 140 mesh or any two of these.

[0042] In this invention, the quartz sand is controlled to have a particle size of 70-140 mesh, which ensures that the particles have a suitable gradation for packing and forming, and can also form a relatively uniform and dense structure during subsequent melting or sintering. This is beneficial for obtaining a stable load-bearing skeleton for the outer layer or support layer of the crucible. If the particle size is too coarse, the gaps between particles will increase, resulting in uneven sintering shrinkage and interfacial bonding; if the particle size is too fine, it will easily cause agglomeration, decreased permeability, and forming defects. Therefore, limiting the particle size to 70-140 mesh achieves a balance between formability, densification efficiency, and thermal stability.

[0043] In some embodiments, the purity of the quartz sand is ≥99.9999%, for example, it can be a range of 99.9999%, 99.99991%, 99.99992%, 99.99993%, 99.99994%, 99.99995%, 99.99996%, 99.99997%, 99.99998%, 99.99999%, or any two of these.

[0044] The purity of quartz sand is controlled to be ≥99.9999%, or ≥6N, which can significantly reduce the risk of contamination of silicon liquid and high-temperature structures by impurities such as Na, K, Al, Ca, and Ba, and prevent impurities from migrating and inducing lattice defects or softening instability in service environments above 1500℃.

[0045] In some embodiments, the hydroxyl content in the quartz sand is 1 to 20 ppm, for example, it can be a range of 1 ppm, 3 ppm, 5 ppm, 8 ppm, 10 ppm, 15 ppm, 20 ppm or any two of these.

[0046] Controlling the hydroxyl content in quartz sand to a low ppm level can reduce volatilization, porosity formation, and localized stress concentration caused by hydroxyl removal at high temperatures. Specifically, low hydroxyl content means fewer internally releaseable components, making the material less prone to microcracks and structural relaxation during long-term thermal cycling, thereby improving the crucible's service stability.

[0047] Through the synergistic control of particle size, purity, and hydroxyl content, quartz sand can ensure both high packing density and uniform sintering behavior, while maintaining high purity and low gas release characteristics. This results in better high-temperature load-bearing capacity, thermal shock resistance, and service life in the outer and support layers of semiconductor-grade quartz crucibles.

[0048] Secondly, the present invention provides a method for preparing the quartz sand as described above, comprising the following steps:

[0049] In-situ seeding was performed on a raw material system comprising silicate hydrolysate sol, cristobalite crystal nucleus suspension, and acidic catalyst to obtain a doped gel.

[0050] The doped gel was subjected to aging and sintering treatments in sequence to obtain quartz sand.

[0051] In this invention, a cristobalite crystal nucleus suspension can be slowly added to a silicate ester hydrolysis sol under stirring conditions, and an acidic catalyst can be introduced simultaneously to control the hydrolysis and condensation rates, so that the cristobalite crystal nuclei can be uniformly dispersed and coated by the gel network, thereby forming a structurally stable doped gel.

[0052] Aging treatment is typically carried out in a closed or humid environment to allow the gel to continue condensing, expel pore fluid, and strengthen the network, thereby fixing the position of the cristobalite nuclei within the silica matrix. Subsequent sintering, after removing organic residues and volatile components, completes densification and phase rearrangement at high temperatures, transforming the gel into quartz sand that meets the requirements while maintaining the internal cristobalite nucleus structure.

[0053] This invention, through in-situ inoculation of silicate hydrolysis sol, cristobalite nucleus suspension, and acidic catalyst, enables cristobalite nuclei to be uniformly embedded in the silica network in the early stages of the sol-gel transition. This allows for continuous coating during the aging stage and stable retention as internal crystallization centers during sintering. Specifically, acid-catalyzed hydrolysis-condensation lowers the reaction threshold of the silicate system and improves gel uniformity, while the internal nuclei provide directional nucleation sites for subsequent high-temperature crystallization, thereby suppressing the introduction of exogenous impurities and localized surface crystallization. Because the nuclei are distributed within the matrix, the sintered quartz sand exhibits a more uniform phase structure and thermal expansion response at the particle size scale, reducing stress concentration, microcracks, and spalling risks during high-temperature service. This achieves a synergistic balance between high purity, uniform crystallization, and high-temperature stability, and provides a suitable material basis for the quartz sand used in the outer and support layers of the quartz crucible.

[0054] In this invention, the cristobalite crystal nucleus suspension can be added dropwise to the stirred silicate hydrolysate sol, which facilitates more uniform dispersion. Alternatively, the cristobalite crystal nucleus suspension can be premixed with a portion of the silicate hydrolysate sol before being mixed with the remaining silicate hydrolysate sol, making it suitable for large-scale continuous production. Furthermore, the cristobalite crystal nucleus suspension and silicate hydrolysate sol can be simultaneously atomized and mixed using a spray drying method, resulting in a more uniform crystal nucleus distribution.

[0055] In this invention, after the aging treatment, a washing treatment and a drying treatment may be included. The washing treatment may employ ultrapure water for multi-stage reverse washing until the washing solution is neutral and free of residual impurity ions. The multi-stage reverse washing process can efficiently remove residual catalyst ions (e.g., Cl-) from the gel.- Or NO3 - At the same time, reduce the amount of ultrapure water used.

[0056] The drying process involves naturally drying the washed gel at 80–150°C using a stepped temperature increase or in an oven; or supercritical CO2 drying (critical parameters set at 40–60°C and 7.38–10 MPa). Freeze-drying can also be used, where the washed gel is pre-frozen at -40–-80°C and then sublimated under vacuum. Freeze-drying maximizes the preservation of the gel's porous network structure and reduces volume shrinkage and crystal segregation during the drying process. Microwave drying can also be used, achieving rapid and uniform drying and shortening the drying time. Infrared drying can also be employed, using infrared radiation heating to achieve simultaneous surface and internal drying, reducing surface crusting.

[0057] In some embodiments of the present invention, the mass fraction of quartz crystal nuclei in the quartz crystal nuclei suspension is 0.1-5% of the silica in the raw material system. For example, it can be 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, or any combination thereof.

[0058] The above-mentioned range can provide sufficient heterogeneous nucleation centers while avoiding excessive crystal nuclei that could lead to local agglomeration of the gel, uneven structure, or subsequent sintering cracking.

[0059] When the amount of cristobalite crystal nuclei added is less than 0.1%, the number of crystal nuclei is insufficient, and sufficient bulk crystallization induction cannot be achieved; when the amount added is more than 5%, the crystal nuclei are too dense, which can easily lead to agglomeration and affect the continuity of the amorphous matrix and the purity of the final product.

[0060] In some embodiments, the in situ inoculation temperature is 40~70°C, for example, it can be a range of 40°C, 45°C, 50°C, 60°C, 70°C or any two of them; the in situ inoculation time is 2~12h, for example, it can be a range of 2h, 6h, 8h, 10h, 12h or any two of them.

[0061] The temperature and time settings for in-situ inoculation are used to regulate the sol-gel polymerization rate and the crystal nucleus embedding efficiency. A temperature range of 40–70°C balances system flowability and gelation rate, while 2–12 hours is sufficient to complete crystal nucleus dispersion, interfacial adsorption, and preliminary network fixation, thereby forming a doped gel containing cristobalite crystal nuclei. This facilitates the uniform embedding of cristobalite crystal nuclei into the silica matrix during the sol-gel network formation process.

[0062] In some embodiments of the present invention, the cristobalite nucleus suspension is obtained by dispersing cristobalite nuclei in a solvent and ultrasonically treating them for 30 to 90 minutes (e.g., a range of 500W, 600W, 700W, 900W, 1000W, 1200W, or any combination thereof) at a power of 500 to 1200W (e.g., a range of 30 minutes, 40 minutes, 50 minutes, 60 minutes, 70 minutes, 80 minutes, 90 minutes, or any combination thereof). The solvent includes at least one of anhydrous ethanol, ultrapure water, isopropanol, acetone, and ethylene glycol.

[0063] Quadritic quartz nanocrystals have high surface energy, making them prone to agglomeration in subsequent sol-gel systems. Insufficient ultrasonic power (<500W) is ineffective in breaking up agglomerates; excessive ultrasonic power (>1200W) causes the dispersion medium to heat up and volatilize, affecting system stability. An ultrasonic treatment time of 30–90 minutes ensures that the crystal nuclei achieve a highly stable dispersion state, creating conditions for subsequent in-situ uniform inoculation.

[0064] The Dv50 of the cristobalite crystal nucleus is ≤1μm, for example, it can be a range of 0.1μm, 0.3μm, 0.5μm, 0.7μm, 0.9μm, 1μm or any two of these.

[0065] In this invention, the Dv50 of the cristobalite crystal nuclei can be ≤1μm by ultrapure airflow pulverization or high-purity quartz media ball milling.

[0066] The preparation of the cristobalite crystal nucleus suspension can be carried out by pre-weighing the cristobalite crystal nuclei and then adding them to the selected solvent for wet dispersion. The amount of cristobalite crystal nuclei added can be adjusted according to the required crystal nucleus concentration for subsequent in-situ inoculation. The solvent can be any one of anhydrous ethanol, ultrapure water, isopropanol, acetone, or ethylene glycol, or two or more of these can be mixed in any proportion to balance wettability, evaporation rate, and dispersion stability. Anhydrous ethanol, isopropanol, and acetone are beneficial for reducing the surface tension of the system, ultrapure water is beneficial for maintaining the cleanliness of the system, and ethylene glycol is beneficial for improving suspension stability. After adding the cristobalite crystal nuclei to the solvent, they are first mechanically stirred or pre-dispersed at low speed to achieve initial wetting, and then subjected to ultrasonic treatment at 500~1200W for 30~90 minutes. This allows the agglomerated particles to deagglomerate under cavitation shearing and form a uniform suspension, ensuring dispersion efficiency while avoiding excessive ultrasonication that could lead to localized heating, secondary particle agglomeration, or damage to the crystal nucleus structure. To ensure that the crystal nuclei can be stably suspended and suitable for subsequent in-situ seeding, the Dv50 of the cristobalite crystal nuclei is controlled to be 1 μm or less. Here, Dv50 represents the median particle size corresponding to the cumulative distribution in the particle volume distribution reaching 50%. Using this particle size range can give the crystal nuclei a higher specific surface area and higher nucleation activity, which is convenient for the formation of uniformly dispersed heterogeneous nucleation centers in silicate hydrolysate sol.

[0067] In this invention, the preparation of the cristobalite nucleus suspension aims to stably introduce small, uniformly dispersed cristobalite nuclei into the raw material system during subsequent in-situ seeding, thereby ensuring the spatial uniformity of the nuclei's distribution within the gel network. By first dispersing the cristobalite nuclei in at least one solvent selected from anhydrous ethanol, ultrapure water, isopropanol, acetone, or ethylene glycol, and then applying ultrasonic energy of 500–1200 W for 30–90 min, the microjets and shear forces generated by ultrasonic cavitation can disrupt van der Waals aggregation and electrostatic bridging between the nuclei, reducing the particle size and resulting in a narrower distribution. Specifically, Dv50 ≤ 1 μm allows the nuclei to migrate more uniformly with the mobile phase during the sol stage, reducing sedimentation and local enrichment, thereby improving the uniformity of the nuclei distribution within the subsequent doped gel. Because the selected solvent has good compatibility and purity with the dispersion medium, it can reduce the risk of introducing foreign impurities, thus meeting the preparation requirements of the high-purity quartz sand system. Furthermore, by limiting the ultrasonic power and time within the aforementioned range, a balance can be achieved between deagglomeration efficiency, suspension stability, and crystal nucleus integrity. This results in a suspension with sufficiently low agglomeration while maintaining good mass transfer and mixing during in-situ inoculation, thus providing a foundation for ultimately obtaining quartz sand containing cristobalite crystal nuclei and achieving a balance between purity and structural stability. Based on the above analysis, it can be seen that this suspension preparation method, through the synergistic effect of particle size control, solvent selection, and ultrasonic dispersion, can effectively improve the crystal nucleus utilization rate and suppress subsequent uneven crystallization.

[0068] In some embodiments of the present invention, cristobalite nuclei are obtained by devitrifying amorphous silicon dioxide.

[0069] The devitrification reaction includes: heating amorphous silicon dioxide to 1300-1500°C at a heating rate of 2-5°C / min (for example, a range of 2°C / min, 3°C / min, 4°C / min, 5°C / min or any combination thereof) for 4-12 hours in an oxygen-containing atmosphere (clean air atmosphere or oxygen-enriched atmosphere) to obtain cristobalite crystal nuclei.

[0070] For example, the temperature of the devitrification reaction is a range of 1300°C, 1350°C, 1400°C, 1450°C, 1500°C or any two of these; the time of the devitrification reaction is a range of 4h, 6h, 8h, 10h, 12h or any two of these.

[0071] The devitrification (phase transition) of amorphous silica to cristobalite is a kinetic process that requires overcoming a relatively high potential barrier. 1300℃ is the lower limit of the critical temperature for the phase transition to begin, while 1500℃ ensures complete phase transition. A reaction time of 4 hours is the lower limit for ensuring complete bulk phase transition; exceeding 12 hours is unnecessary and wasteful of energy. The heating rate is controlled at 2~5℃ / min because amorphous silica powder has a large specific surface area; excessively rapid heating can easily lead to sintering and pore closure on the particle surface, hindering the expulsion of internal moisture and residual gases. Clean air or an oxygen-rich atmosphere helps to burn off any trace carbon impurities that may remain in the amorphous silica, ensuring the high purity of the final product.

[0072] The Dv50 of amorphous silicon dioxide is ≤50μm, for example, it can be a range of 1μm, 10μm, 20μm, 30μm, 40μm, 50μm or any combination thereof.

[0073] In some embodiments, the purity of amorphous silica is ≥99.9%, for example, it can be a range of 99.9%, 99.92%, 99.94%, 99.95%, 99.97%, 99.99%, or any two of these.

[0074] In some embodiments, amorphous silica is derived from waste generated during the production of high-purity silica materials.

[0075] The waste material itself belongs to the high-purity SiO2 system. Direct disposal would result in resource waste. However, if it is transformed into pure quartz through appropriate heat treatment and then used as a crystal nucleus, high-value utilization can be achieved without introducing new foreign impurities. At the same time, the zero-value waste is transformed into a high-end crystal nucleus additive, realizing a closed-loop high-value-added utilization of waste and significantly reducing the overall production cost of the system.

[0076] In this invention, amorphous silica is not limited to waste powder generated from the crushing process of sol-gel synthesis of quartz sand, but can also come from ultrafine waste powder generated during the acid washing and purification process of natural quartz sand; it can also come from grinding waste powder generated during the processing of quartz glass products; and it can also come from waste materials generated during the production of other high-purity silica materials (such as fumed silica and precipitated silica).

[0077] In this invention, amorphous silica with a Dv50 ≤ 50 μm and a purity ≥ 99.9% is used as a precursor. Preferably, amorphous waste generated during the production of high-purity silica materials is used. After screening, impurity removal, and drying, the waste is fed into a devitrification furnace. Under an oxygen-containing atmosphere, the temperature is slowly increased to 1300-1500℃ at a heating rate of 2-5℃ / min and held for 4-12 hours, causing the glassy structure to gradually rearrange and form cristobalite crystal nuclei within the bulk phase. By controlling Dv50 to be no greater than 50 μm, the uniformity of heat and mass transfer can be increased, the internal temperature difference of the particles can be reduced, and simultaneous crystallization can be promoted. By controlling the purity to above 99.9%, unintended nucleation and phase transformation shifts caused by impurities such as sodium, potassium, iron, and aluminum can be suppressed, thereby improving the purity and repeatability of the cristobalite crystal nuclei. Using production waste as raw material allows for high-value utilization while maintaining high purity, reducing raw material costs.

[0078] Specifically, when amorphous silica is heated in an oxygen-containing atmosphere, the silicon-oxygen network gradually relaxes and undergoes localized ordered rearrangement. When the temperature reaches 1300–1500℃, the thermodynamic driving force within the system is sufficient to promote the preferential nucleation of the cristobalite phase. During the 4–12 hour holding period, the crystal nuclei continue to grow and complete the transformation from an amorphous structure to a cristobalite crystal structure. Holding for more than 4 hours ensures sufficient reaction, while holding for less than 12 hours avoids excessive grain growth and agglomeration. The oxygen-containing atmosphere maintains the stability of the system's chemical environment, reduces the disturbance of the Si-O bond structure by reducing impurities, and facilitates the removal of volatile impurities, thereby forming cristobalite crystal nuclei with controllable size and stable crystal phase. This process achieves the goal of in-situ conversion of high-purity amorphous silica waste into cristobalite crystal nuclei, allowing the obtained nuclei to serve as nucleation centers within subsequent quartz sand, thereby improving the uniformity and stability of high-temperature crystallization of quartz sand and reducing thermal stress concentration caused by localized crystallization.

[0079] In some embodiments of the present invention, the silicate ester hydrolysate sol is obtained by mixing silicate ester and ultrapure water at a molar ratio of (4~10):1, adding a hydrolysis catalyst, and carrying out a hydrolysis reaction at a pH of 1.5~3.0 and a temperature of 40~70°C.

[0080] For example, the molar ratio of silicate to ultrapure water is 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, or any combination thereof; the pH of the hydrolysis reaction is 1.5, 1.8, 2.0, 2.5, 2.8, 3.0, or any combination thereof; and the temperature of the hydrolysis reaction is 40°C, 45°C, 50°C, 55°C, 60°C, 70°C, or any combination thereof.

[0081] In this invention, the molar ratio of silicate ester to ultrapure water is controlled at (4~10):1, which ensures that the hydrolysis rate matches the polycondensation rate, avoiding localized excessively rapid gelation or incomplete hydrolysis that could result in coarse particles. Ultrapure water is used to reduce the risk of metal ion introduction, ensuring that the subsequently formed silicate ester hydrolysate sol meets the requirements of a high-purity system. The amount of hydrolysis catalyst added is used to adjust the pH of the system to 1.5~3.0 to promote controlled hydrolysis of the silicate ester and inhibit disordered polycondensation. The sol is typically prepared at 40~70℃, and mass transfer can be maintained uniformly through constant-temperature stirring, allowing silanol groups to gradually form and create a sol system with uniform particle size.

[0082] Specifically, silicates undergo stepwise hydrolysis under acid catalysis and in the presence of an appropriate amount of water, generating active silanol groups and forming a dispersed and stable oligomeric silica network. The molar ratio, pH, and temperature together define the kinetic window for hydrolysis and polycondensation, thus giving the sol suitable reactivity and uniformity. By controlling the degree of hydrolysis within a range that allows for gelation but not excessive aggregation, a continuous and uniform silicon source basis can be provided for subsequent in-situ inoculation with cristobalite crystal nucleus suspension. This reduces the probability of local concentration gradients and structural defects, resulting in quartz sand that maintains ultra-high purity while possessing a more stable internal crystal nucleus distribution and more controllable crystallization behavior. This meets the requirements of semiconductor-grade quartz crucible materials for high-temperature stability, structural uniformity, and service reliability.

[0083] In some embodiments of the present invention, the hydrolysis catalyst includes at least one of hydrochloric acid and nitric acid.

[0084] In some embodiments, the silicate ester includes at least one of methyl silicate, ethyl silicate, propyl silicate, and butyl silicate.

[0085] In this invention, the hydrolysis catalyst can be hydrochloric acid or nitric acid alone, or any combination of the two, to stably control the pH of the system within the acidic range of 1.5 to 3.0 at a low addition amount, thereby accelerating the hydrolysis and polycondensation initiation rate of the silicate ester and inhibiting localized excessively rapid gelation. The silicate ester can be at least one of methyl silicate, ethyl silicate, propyl silicate, and butyl silicate, preferably a low-carbon-number silicate ester, so that it can undergo controlled hydrolysis with ultrapure water at 40-70°C to form a silicate hydrolysate sol with more uniform particle size and lower impurity introduction. Since both hydrochloric acid and nitric acid are strongly acidic and have low decomposition residues, they can reduce the risk of metal ion contamination. Furthermore, different silicate esters exhibit varying alkoxy hydrolysis activities; using a single type or a combination can be used to adjust the hydrolysis rate, polycondensation kinetics, and sol stability, thus facilitating subsequent in-situ seeding with cristobalite crystal nuclei suspension to form a uniformly structured doped gel.

[0086] In some embodiments of the present invention, the aging treatment temperature is 50~80°C, for example, it can be a range of 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C or any two of these; the aging treatment time is 12~24h, for example, it can be a range of 12h, 14h, 16h, 18h, 20h, 22h, 24h or any two of these.

[0087] In some embodiments, the sintering process includes: first performing a first sintering treatment on the aged doped gel at 600~900°C for 2~4 hours, and then performing a second sintering treatment at 1050~1150°C for 2~6 hours.

[0088] For example, the temperature of the first sintering treatment is a range of 600°C, 650°C, 700°C, 750°C, 800°C, 900°C, or any two of these; the time of the first sintering treatment is a range of 2h, 2.5h, 3h, 3.5h, 4h, or any two of these; the temperature of the second sintering treatment is a range of 1050°C, 1070°C, 1090°C, 1100°C, 1120°C, 1150°C, or any two of these; and the time of the second sintering treatment is a range of 2h, 2.5h, 3h, 3.5h, 4h, 5h, 6h, or any two of these.

[0089] In this invention, after in-situ seeding, the doped gel enters an aging process, which is preferably carried out at 50-80°C for 12-24 hours. This allows the sol network formed by the hydrolysis of silicate esters to further condense and stabilize the internal microstructure, preventing excessively rapid dehydration shrinkage or local collapse during subsequent heating. The aged doped gel then undergoes segmented sintering. The first sintering is completed at 600-900°C for 2-4 hours, gradually removing residual organic groups, adsorbed water, and low-boiling-point byproducts, and promoting initial densification of the gel framework. The second sintering is then completed at 1050-1150°C for 2-6 hours, further rearranging the silica matrix and forming a stable crystalline structure around the internal cristobalite nucleus. Based on the above analysis, the synergistic effect of aging and segmented sintering can, without introducing additional impurities, gradually transform the doped gel from a wet gel state into quartz sand with internal cristobalite nuclei.

[0090] Specifically, the aging process mainly promotes the condensation reaction between silanol groups through gentle heating, further converting Si-OH in the gel into Si-O-Si bonds, thereby improving network continuity and reducing internal stress. If the temperature is below 50℃, the condensation rate is insufficient, which can easily lead to low gel strength. If the temperature is above 80℃, it may cause excessively rapid dehydration and uneven pore closure, affecting the uniformity of subsequent sintering. For the sintering process, the first sintering temperature zone is set at 600~900℃, which allows the gel to retain the nucleation effect of cristobalite crystal nuclei while eliminating volatile components, avoiding crystal nucleus deactivation at low temperatures. The second sintering temperature zone is set at 1050~1150℃, which provides sufficient phase transformation driving force to promote the ordered rearrangement of the silica matrix under the induction of crystal nuclei, forming a stable internal crystalline phase. Thus, the doped gel undergoes devolatilization, densification, and crystallization transformations in a controlled thermal process, ultimately yielding high-purity, uniform quartz sand with internal cristobalite crystal nuclei, thereby improving its crystallization consistency, structural stability, and thermal shock resistance under high-temperature service conditions.

[0091] The quartz sand prepared by this invention is not only suitable for the outer layer and support layer of semiconductor-grade quartz crucibles, but also for high-purity quartz materials in the manufacture of optical fiber preforms, raw materials for high-end optical quartz glass products, and other quartz ceramic materials that require high-temperature stability and ultra-high purity.

[0092] The technical solution of the present invention will be further described below with reference to specific embodiments.

[0093] Example 1

[0094] The method for preparing quartz sand in this embodiment includes the following steps:

[0095] 1) Amorphous ultrafine powder, namely amorphous silica (Dv50=35μm, purity 99.9999%), produced during the crushing and screening process of sol-gel synthesized quartz sand, was collected and placed in a high-temperature furnace. Under clean air, it was heated to 1400℃ at a heating rate of 3℃ / min for 8 hours to undergo devitrification, yielding cristobalite crystal nuclei. XRD analysis showed that the cristobalite phase content was >95%.

[0096] 2) The cristobalite nuclei obtained in step 1) were pulverized with ultrapure airflow to a Dv50 of 0.5 μm. They were then dispersed in ultrapure water and ultrasonically treated at 800 W for 60 min to prepare a uniform and stable cristobalite nuclei suspension.

[0097] 3) Tetraethyl silicate (TEOS) was mixed with ultrapure water at a molar ratio of 6:1, and high-purity electronic-grade hydrochloric acid was added as a hydrolysis catalyst to obtain the raw material system. The pH of the raw material system was controlled at 2.0, and the hydrolysis reaction was carried out at 55℃ for 4 hours to prepare TEOS hydrolyzed sol.

[0098] 4) The cristobalite nucleus suspension prepared in step 2) is uniformly incorporated into the TEOS hydrolyzed sol, wherein the cristobalite nucleus in the cristobalite nucleus suspension accounts for 1.0% of the mass fraction of silica in the raw material system. The raw material system is stirred and mixed at 55°C for 6 hours for in-situ inoculation to form a three-dimensional gel network encapsulating cristobalite nucleus, i.e., a doped gel.

[0099] 5) The doped gel was aged in a sealed environment at 65°C for 18 hours; it was then washed in a multi-stage reverse sequence with ultrapure water until the washing solution was neutral and free of chloride ions; it was dried in an oven at 120°C for 8 hours; a first sintering treatment was performed at 800°C for 3 hours; a second sintering treatment was performed at 1100°C for 4 hours; after cooling, it was crushed and sieved to obtain a crystalline high-purity synthetic quartz sand product with a particle size of 70~140 mesh.

[0100] Quartz sand comprises a silica matrix and cristobalite crystal nuclei located within the silica matrix.

[0101] Example 2

[0102] The preparation method of the quartz sand in this embodiment is basically the same as that in Example 1, except that in step 1), the temperature of the devitrification reaction is 1300℃ and the time is 12h.

[0103] Example 3

[0104] The preparation method of the quartz sand in this embodiment is basically the same as that in Example 1, except that in step 1), the temperature of the devitrification reaction is 1500℃ and the time is 4h.

[0105] Example 4

[0106] The preparation method of quartz sand in this embodiment is basically the same as that in Example 1. The difference is that in step 2), the cristobalite crystal nuclei obtained in step 1) are pulverized with ultrapure airflow to Dv50=0.2μm.

[0107] Example 5

[0108] The preparation method of quartz sand in this embodiment is basically the same as that in Example 1. The difference is that in step 2), the cristobalite crystal nuclei obtained in step 1) are pulverized with ultrapure airflow to Dv50=0.8μm.

[0109] Example 6

[0110] The preparation method of quartz sand in this embodiment is basically the same as that in Example 1. The difference is that in step 4), the mass fraction of quartz crystal nuclei in the quartz crystal nuclei suspension is 0.5% of the silica in the raw material system.

[0111] Example 7

[0112] The preparation method of quartz sand in this embodiment is basically the same as that in Example 1. The difference is that in step 4), the mass fraction of quartz crystal nuclei in the quartz crystal nuclei suspension is 3% of the silica in the raw material system.

[0113] Example 8

[0114] The preparation method of quartz sand in this embodiment is basically the same as that in Example 1, except that in step 5), the temperature of the second sintering treatment is 1050℃ and the time is 6h.

[0115] Example 9

[0116] The preparation method of quartz sand in this embodiment is basically the same as that in Example 1, except that in step 5), the temperature of the second sintering treatment is 1150℃ and the time is 2h.

[0117] Example 10

[0118] The preparation method of the quartz sand in this embodiment is basically the same as that in Example 1. The difference is that in step 3), methyl silicate (TMOS) and ultrapure water are mixed at a molar ratio of 4:1, and high-purity electronic-grade hydrochloric acid is added as a hydrolysis catalyst to control the pH value of the system to 1.5.

[0119] Example 11

[0120] The preparation method of the quartz sand in this embodiment is basically the same as that in Example 1, except that in step 3), methyl silicate (TMOS) and ultrapure water are mixed at a molar ratio of 5:1, and high-purity electronic-grade nitric acid is added as a hydrolysis catalyst to obtain the raw material system. The pH value of the raw material system is controlled at 2.5, and the hydrolysis reaction is carried out at 50°C for 3 hours to prepare TMOS hydrolyzed sol.

[0121] In step 4), the cristobalite nucleus suspension prepared in step 2) is uniformly incorporated into the TMOS hydrolytic sol, wherein the cristobalite nuclei in the cristobalite nucleus suspension account for 2.0% of the mass fraction of silicon dioxide in the raw material system. The raw material system is stirred and mixed at 50°C for 8 hours for in-situ seeding, forming a three-dimensional gel network encapsulating cristobalite nuclei, i.e., a doped gel.

[0122] In step 5), the doped gel is aged in a sealed environment at 70°C for 16 hours; it is then washed in a multi-stage reverse sequence with ultrapure water until the washing solution is neutral and free of nitrate ions; it is dried with supercritical CO2 (temperature 45°C, pressure 8MPa, drying time 4 hours); a first sintering treatment is performed at 750°C for 3 hours; a second sintering treatment is performed at 1100°C for 4 hours; after cooling, it is crushed and sieved to obtain a crystalline high-purity synthetic quartz sand product with a particle size of 70~140 mesh.

[0123] Example 12

[0124] The preparation method of quartz sand in this embodiment is basically the same as that in Example 1, except that in step 2), the cristobalite crystal nuclei obtained in step 1) are pulverized with ultrapure airflow to a Dv50 of 0.6 μm. They are then dispersed in anhydrous ethanol and ultrasonically treated at 600 W for 45 min to prepare a uniform and stable cristobalite crystal nuclei suspension.

[0125] In step 3), propyl silicate and ultrapure water are mixed at a molar ratio of 8:1, and high-purity electronic-grade hydrochloric acid is added as a hydrolysis catalyst to obtain the raw material system. The pH of the raw material system is controlled at 2.8, and the hydrolysis reaction is carried out at 60℃ for 5 hours to prepare propyl silicate hydrolysate sol.

[0126] In step 4), the cristobalite nucleus suspension prepared in step 2) is uniformly incorporated into the propyl silicate hydrolysate sol, wherein the cristobalite nucleus in the cristobalite nucleus suspension accounts for 1.5% of the mass fraction of silica in the raw material system. The raw material system is stirred and mixed at 60°C for 5 hours for in-situ inoculation, forming a three-dimensional gel network encapsulating the cristobalite nucleus, i.e., a doped gel.

[0127] In step 5), the doped gel is aged in a sealed environment at 75°C for 14 hours; it is then washed in a multi-stage reverse sequence with ultrapure water until the washing solution is neutral and free of chloride ion residue; the washed doped gel is pre-frozen at -60°C for 6 hours, and then freeze-dried under vacuum conditions (vacuum degree <10Pa, drying time 24 hours); a first sintering treatment is performed at 850°C for 3 hours; a second sintering treatment is performed at 1100°C for 4 hours; after cooling, it is crushed and sieved to obtain a crystalline high-purity synthetic quartz sand product with a particle size of 70~140 mesh.

[0128] Example 13

[0129] The preparation method of quartz sand in this embodiment is basically the same as that in Example 1, except that in step 2), the cristobalite nuclei obtained in step 1) are ball-milled in high-purity quartz media until Dv50 = 0.7 μm. They are then dispersed in ultrapure water and ultrasonically treated at 1000 W ultrasonic power for 50 min to prepare a uniform and stable cristobalite nuclei suspension.

[0130] In step 3), tetraethyl orthosilicate (TEOS) and ultrapure water are mixed at a molar ratio of 7:1, and high-purity electronic-grade nitric acid is added as a hydrolysis catalyst to obtain the raw material system. The pH of the raw material system is controlled at 1.8, and the hydrolysis reaction is carried out at 45°C for 6 hours to prepare TEOS hydrolyzed sol.

[0131] In step 4), the cristobalite nucleus suspension prepared in step 2) is uniformly incorporated into the TEOS hydrolyzed sol, wherein the cristobalite nucleus in the cristobalite nucleus suspension accounts for 0.8% of the mass fraction of silica in the raw material system. The raw material system is stirred and mixed at 45°C for 10 hours for in-situ inoculation, forming a three-dimensional gel network encapsulating the cristobalite nucleus, i.e., a doped gel.

[0132] In step 5), the doped gel is aged in a sealed environment at 60°C for 20 hours; it is then washed in a multi-stage reverse sequence with ultrapure water until the washing solution is neutral and free of nitrate ions; it is then dried using microwave (power 400W, drying time 2 hours); a first sintering treatment is performed at 700°C for 4 hours; a second sintering treatment is performed at 1100°C for 6 hours; after cooling, it is crushed and sieved to obtain a crystalline high-purity synthetic quartz sand product with a particle size of 70~140 mesh.

[0133] Example 14

[0134] The preparation method of quartz sand in this embodiment is basically the same as that in Example 1. The difference is that in step 4), the mass fraction of quartz crystal nuclei in the quartz crystal nuclei suspension is 0.09% of the silica in the raw material system.

[0135] Example 15

[0136] The preparation method of quartz sand in this embodiment is basically the same as that in Example 1. The difference is that in step 4), the mass fraction of quartz crystal nuclei in the quartz crystal nuclei suspension is 4.8% of the silica in the raw material system.

[0137] Example 16

[0138] The preparation method of the quartz sand in this embodiment is basically the same as that in Example 1, except that in step 1), the temperature of the devitrification reaction is 1100℃ and the time is 8h.

[0139] Example 17

[0140] The preparation method of the quartz sand in this embodiment is basically the same as that in Example 1, except that in step 1), the temperature of the devitrification reaction is 1600℃ and the time is 20h.

[0141] Example 18

[0142] The preparation method of quartz sand in this embodiment is basically the same as that in Example 1. The difference is that in step 2), the cristobalite crystal nuclei obtained in step 1) are simply ball-milled to Dv50=8μm.

[0143] Example 19

[0144] The preparation method of quartz sand in this embodiment is basically the same as that in Example 1. The difference is that in step 4), the mass fraction of quartz crystal nuclei in the quartz crystal nuclei suspension is 0.05% of the silica in the raw material system.

[0145] Example 20

[0146] The preparation method of quartz sand in this embodiment is basically the same as that in Example 1. The difference is that in step 4), the mass fraction of quartz crystal nuclei in the quartz crystal nuclei suspension is 8% of the silica in the raw material system.

[0147] Example 21

[0148] The preparation method of quartz sand in this embodiment is basically the same as that in Example 1, except that in step 5), the temperature of the second sintering treatment is 900℃ and the time is 8h.

[0149] Example 22

[0150] The preparation method of quartz sand in this embodiment is basically the same as that in Example 1, except that in step 5), the temperature of the second sintering treatment is 1250℃ and the time is 4h.

[0151] Comparative Example 1

[0152] The preparation method of the quartz sand in this comparative example is basically the same as that in Example 1, except that in step 3), analytical grade ammonia is used instead of high-purity electronic-grade hydrochloric acid as the hydrolysis catalyst, and the pH value of the system is controlled to be 9.0~10.0. Ultimately, the cristobalite crystal nuclei cannot be effectively encapsulated.

[0153] Comparative Example 2

[0154] The preparation method of the comparative example and the quartz sand in Example 1 is basically the same, except that steps 1), 2) and 4) are omitted, and only pure TEOS hydrolyzed sol is used for gelation and subsequent treatment. The product obtained is pure amorphous quartz sand.

[0155] Comparative Example 3

[0156] The preparation method of the quartz sand in this comparative example follows the physical blending method of the prior art: pure amorphous quartz sand (prepared by the same method as in comparative example 2) is dry mechanically mixed with commercially available micron-sized cristobalite powder (Dv50=10μm) at a mass ratio of 99:1.

[0157] Experimental example:

[0158] Quartz crucible sample preparation: The quartz sand obtained in each embodiment or comparative example was used as the raw material for the outer layer and support layer of the quartz crucible, and conventional semiconductor-grade high-purity amorphous quartz sand was used as the inner layer raw material. Following the conventional vacuum arc melting process for quartz crucibles, the inner layer raw material was laid on the inner surface of a rotating mold, and the quartz sand to be tested was laid on the outer side of the inner layer. After vacuuming, electricity was applied to melt and form the sample. After cooling and demolding, the quartz crucible sample was obtained.

[0159] The quartz sand to be tested is located in the middle and outer layers and the support layer of the quartz crucible. It is used to form a uniform cristobalite crystallization skeleton during high-temperature use, thereby improving the resistance to softening deformation and high-temperature strength of the outer load-bearing structure of the crucible.

[0160] 1. Crystallization rate: Quartz sand samples obtained from each example or comparative example were heated to 1500℃ and held for 4 hours in a clean air atmosphere. After cooling, they were ground to the particle size required for XRD testing. The phase composition of the samples was tested using an X-ray diffractometer, and the mass fraction of the cristobalite phase was calculated by Rietveld full-spectrum fitting. This mass fraction was taken as the cristobalite crystallization rate of the quartz sand after being held at 1500℃ for 4 hours.

[0161] 2. Bending strength: Strip specimens were cut from the middle and outer layers / support layers of the above-mentioned quartz crucible samples. After being kept at 1500℃, the high-temperature bending strength was tested according to the three-point bending method. Five specimens were tested in each group, and the average value was taken as the high-temperature bending strength of the quartz crucible at 1500℃.

[0162] 3. Purity and hydroxyl content: The purity of quartz sand was determined by ICP-MS of the acid-digested sample to detect impurity elements and to calculate the SiO2 purity. The hydroxyl content was determined by Fourier transform infrared spectroscopy and calculated based on the characteristic absorption peak of hydroxyl groups. The results are expressed in ppm.

[0163] 4. Quartz crucible welding quality: Observe the welding interface between the outer / support layer and the inner layer in the crucible, and evaluate whether there are obvious cracks, bubbles, delamination or unwelded areas in combination with the cross-sectional micromorphology. The evaluation results are divided into excellent, good, average and poor.

[0164] Table 1

[0165]

[0166] As shown in Table 1, compared with the comparative example, the quartz sand provided by the present invention, by setting cristobalite crystal nuclei inside the silica matrix, can provide a stable crystallization basis for the crystallization of quartz sand under high temperature conditions, improve the problem of uneven crystallization caused by preferential crystallization of the surface or local area in the traditional method, thereby improving the uniformity and stability of high temperature crystallization of quartz sand, reducing the risk of thermal expansion mismatch and thermal stress damage caused by differences in crystallization inside and outside or at the interface, and is conducive to improving purity and increasing the strength of quartz crucible.

[0167] The preparation conditions of Examples 16-22 deviated from the preferred subordinate conditions of the present invention. Therefore, the crystallization uniformity, welding quality or high temperature strength of the obtained quartz sand were lower than those of Examples 1-13. However, since the technical route of combining cristobalite crystal nuclei with silica matrix was still adopted, the overall performance was still better than the comparative examples that failed to effectively coat the crystal nuclei, did not set crystal nuclei or adopted physical blending.

[0168] Specifically, in Example 16, the devitrification reaction temperature was relatively low, resulting in insufficient formation of cristobalite crystal nuclei, thus lower crystallization rate and high-temperature flexural strength compared to the preferred embodiment. In Example 17, the devitrification reaction temperature and time were too high, leading to less effective control of crystal nucleus activity and purity compared to the preferred embodiment. In Example 18, the crystal nucleus particle size was large, resulting in decreased dispersion uniformity and reduced crucible strength. In Example 19, the amount of cristobalite crystal nuclei added was too low, resulting in insufficient bulk crystallization induction centers. In Example 20, the amount of cristobalite crystal nuclei added was too high, affecting the uniformity of the gel system and the welding quality. In Example 21, the second sintering temperature was too low, resulting in insufficient gel densification. In Example 22, the second sintering temperature was too high, leading to a higher proportion of crystalline phases formed during the preparation stage of the quartz sand, which reduced subsequent welding compatibility. Although the above examples did not achieve the comprehensive effect of the preferred embodiment, they still exhibited higher crystallization rate and high-temperature flexural strength compared to the comparative examples.

[0169] In Comparative Example 1, the alkaline catalyst led to the formation of spherical SiO2 particles instead of a continuous three-dimensional gel network. The cristobalite crystal nuclei could not be effectively encapsulated and were lost in large quantities during the washing process (loss rate > 60%), resulting in a severe deficiency of cristobalite crystal nuclei in the final quartz sand.

[0170] The quartz sand obtained in Comparative Example 2 was pure amorphous quartz sand. After heating at 1500℃ for 4 hours, the crystallization rate was less than 5%, resulting in low high-temperature bending strength of the quartz crucible.

[0171] In Comparative Example 3, the quartz particles were unevenly distributed after physical mixing, and the thermal expansion coefficients of the phase interfaces were mismatched during crucible melting, resulting in microcracks and low high-temperature bending strength.

[0172] Finally, it should be noted that other embodiments of the invention will readily occur to those skilled in the art upon consideration of the specification and practice of the invention disclosed herein. This invention is intended to cover any variations, uses, or adaptations of the invention that follow the general principles of the invention and include common knowledge or customary techniques in the art not disclosed herein, and is not limited to what has been described above. Various modifications and changes can be made without departing from its scope. The scope of the invention is limited only by the appended claims.

Claims

1. A type of quartz sand, characterized in that, It includes a silicon dioxide matrix and a cristobalite crystal nucleus present inside the silicon dioxide matrix.

2. The quartz sand according to claim 1, characterized in that, The cristobalite nuclei account for 0.1-5% of the mass fraction of the quartz sand.

3. The quartz sand according to claim 1 or 2, characterized in that, The particle size of the quartz sand is 70~140 mesh; And / or, the purity of the quartz sand is ≥99.9999%; And / or, the hydroxyl content in the quartz sand is 1~20ppm.

4. A method for preparing quartz sand as described in any one of claims 1-3, characterized in that, Includes the following steps: In-situ seeding was performed on a raw material system comprising silicate hydrolysate sol, cristobalite crystal nucleus suspension, and acidic catalyst to obtain a doped gel. The doped gel was subjected to aging and sintering treatments in sequence to obtain the quartz sand.

5. The preparation method according to claim 4, characterized in that, The quartz crystal nuclei in the quartz crystal nucleus suspension account for 0.1% to 5% of the mass fraction of silicon dioxide in the raw material system; And / or, the in situ inoculation temperature is 40~70℃, and the in situ inoculation time is 2~12h.

6. The preparation method according to claim 4 or 5, characterized in that, The cristobalite crystal nucleus suspension is obtained by dispersing cristobalite crystal nuclei in a solvent and then ultrasonically treating them at a power of 500~1200W for 30~90 minutes. The solvent includes at least one of anhydrous ethanol, ultrapure water, isopropanol, acetone, and ethylene glycol; The Dv50 of the cristobalite crystal nucleus is ≤1μm.

7. The preparation method according to claim 6, characterized in that, The cristobalite crystal nuclei are obtained by devitrification of amorphous silicon dioxide. The devitrification reaction includes: heating the amorphous silicon dioxide to 1300-1500°C at a heating rate of 2-5°C / min under an oxygen-containing atmosphere, and carrying out the devitrification reaction for 4-12 hours to obtain the cristobalite crystal nucleus; The amorphous silicon dioxide has a Dv50 ≤ 50 μm; And / or, the purity of the amorphous silicon dioxide is ≥99.9%; And / or, the amorphous silica is derived from waste generated during the production of high-purity silica materials.

8. The preparation method according to any one of claims 4-7, characterized in that, The silicate ester hydrolysate sol is obtained by mixing silicate ester and ultrapure water at a molar ratio of (4~10):1, adding a hydrolysis catalyst, and carrying out a hydrolysis reaction at a pH of 1.5~3.0 and a temperature of 40~70℃.

9. The preparation method according to claim 8, characterized in that, The hydrolysis catalyst includes at least one of hydrochloric acid and nitric acid; And / or, the silicate ester includes at least one of methyl silicate, ethyl silicate, propyl silicate, and butyl silicate.

10. The preparation method according to any one of claims 4-9, characterized in that, The aging treatment temperature is 50~80℃, and the aging treatment time is 12~24h; And / or, the sintering process includes: first, subjecting the aged doped gel to a first sintering treatment at 600~900℃ for 2~4h, and then subjecting it to a second sintering treatment at 1050~1150℃ for 2~6h.